Penerapan Konsep Bunga Majemuk dalam Analisis Pertumbuhan Modal Usaha Penjual Sayur di Pasar Tradisional MMTC Medan - Arnah Ritonga; Endang Lyfia Saragih; Grace Amelia Purba; Petra Putri Sarinah Pandiangan; Rizka Nabila Damanik (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study analyzes the application of the compound interest concept in evaluating capital growth among vegetable vendors at the MMTC Traditional Market in Medan, North Sumatra. The research highlights the low level of financial literacy among micro-entrepreneurs in Indonesia, which currently stands at only 38.03%, and its implications for business sustainability. Traditional market traders generally employ basic bookkeeping practices focused solely on daily cash flow, without considering the time value of money or the growth potential from systematic profit reinvestment. Using a mixed-methods approach, this study combines semi-structured interviews to explore existing financial management practices with quantitative modeling based on the discrete compound interest formula to simulate various capital growth scenarios. The analysis reveals that disciplined reinvestment strategies, even when initiated with modest capital and conservative growth rates, can lead to substantial capital accumulation within three to five years. Three primary barriers to capital growth were identified: limited understanding of financial mathematics, lack of long-term planning, and a tendency to prioritize immediate consumption over investment. This research underscores the transformative potential of compound interest principles for micro-enterprise development and recommends practical financial literacy training along with supportive financial ecosystems that encourage sustainable reinvestment practices.